OS02.6.A Lacosamide in monotherapy in brain tumour-related epilepsy (BTRE): results from an Italian multicentre retrospective study. (5th September 2022) - Bruno, F; Mo, F; Meletti, S; Belcastro, V; Quadri, S; Napolitano, M; Bello, L; Dainese, F; Scarpelli, M; Florindo, I; Mascia, A; Pauletto, G; et al.
Abstract: Background: Lacosamide (LCM) is a third-generation anti-seizure medication (ASM) approved for focal onset epilepsy in patients aged ≥4 years. Previous studies have reported an efficacy of LCM as add-on treatment in brain tumour-related epilepsy (BTRE). To date, there are no studies in the literature focusing on lacosamide used in monotherapy to treat BTRE. In our retrospective study we investigated efficacy and tolerability of LCM in monotherapy in a multicentre national cohort of primary brain tumour patients. Patients and Methods: Adult patients who were treated with LCM in monotherapy were collected from 12 Italian Centres (either mainly involved in neuro-oncology or in epileptology). Main inclusion criteria were diagnosis of primary brain tumour; at least two focal-onset seizures in the disease course; LCM used either as primary or secondary monotherapy after withdrawal of previous ASMs. For each patient, we evaluated seizure freedom at 3 and 6 months (primary endpoints), side effects and drop-out rate (secondary endpoints). Results: We collected 132 patients. The majority of patients had a diagnosis of diffuse gliomas, being those with lower-grade glioma 66 (50.0%) and those with glioblastoma 33 (25.0%). Overall, LCM led to seizure-freedom in 64.4% of patients at 3 months and 55% at 6 months. Patients who used two or more ASMs before LCM had a worse seizure control than patients in monotherapy with LCM as first choice.In 14 patients, we observed seizure control despite tumour progression on magnetic resonance (MRI). Multivariate analysis showed that gross-total resection at diagnosis and use of steroids were significantly associated with higher seizure freedom rate at 6 months. Side effects were mainly mild (grade 1-2 according to the CTCAE classification), and the drop-out rate was low (1.5%). The main side effects were dizziness and somnolence. Conclusion: This is the first study on the role of LCM in monotherapy in BTRE. The study has shown a good efficacy and tolerability of LCM with more than a half of patients becoming seizure-free at 6 months and with a very low rate of drop-out. Further studies are needed to confirm these preliminary data in a prospective manner, adding quality of life and neurocognitive functions as endpoints.